Pyoderma gangrenosum arising at the site of BCG immunization in a nine-month-old girl - Yuka Okura; Yasuyoshi Hiramatsu; Masaki Shimomura; Kota Taniguchi; Mitsuru Nawate; Yutaka Takahashi; Masahiro Ueki; Shunichiro Takezaki; Ichiro Kobayashi (Immunological Medicine)
Pyoderma gangrenosum (PG) is an extremely rare disorder in children. We report a nine-month-old girl with PG who presented with high-grade fever and rapidly progressive ulcers at the site of a Bacillus Calmette-Guérin (BCG) inoculation 2 months after the immunization. Additional small pustules developed on her hand and posterior neck three months after the immunization and rapidly progressed. Cytokine profiling demonstrated elevated serum levels of interleukin (IL)-1β, IL-10, IL-17A, IL-6 and IL-18, which is similar to adult cases. Genetic analysis identified heterozygous R202Q variant of the MEFV gene. All of her systemic and local symptoms responded to intravenous methylprednisolone pulse therapy followed by prednisolone 2 mg/kg/day. There is no relapse of PG, to date, even after discontinuation of prednisolone. Atypical skin reactions after a BCG immunization could be an initial manifestation of infantile PG and need attention. Similarity of cytokine profile suggests common pathophysiology of infantile and adult PG.